THE GLORY OF SCIENCE IN CLASSICAL ISLAMIC CIVILIZATION: THE ABBASID DYNASTY AS A CENTER FOR INNOVATION - Erizal Candra Efendi; Wildan Hadi; Sonya Reveny; Nelmawarni (Adisam Publisher, 2025)
The glory of science in classical Islamic civilization, especially during the Abbasid Dynasty, marked the peak of intellectual development in the history of mankind. This dynasty, which ruled from 750 to 1258 AD, became a center of innovation and scientific advancement. Strong support from the Abbasid government, such as the establishment of the Baitul Hikmah educational institution in Baghdad, created a conducive environment for scientific research and development. In addition, an inclusive education system that included various disciplines, such as mathematics, astronomy, medicine, and philosophy, enriched the intellectual treasures of Islam and made a significant contribution to science in Europe during the Renaissance. This study uses a qualitative descriptive method with a phenomenological approach to explore the experiences and perspectives of society during the Abbasid period. The results show that government support, the integration of Islamic values with science, and inclusive education policies play an important role in creating cross-disciplinary innovation. The works of Muslim scientists, such as Al- Khawarizmi, Ibn Sina, and Al-Farabi, not only advanced Islamic civilization but also influenced the development of science in the Western world. This study highlights the relevance of the Abbasid Dynasty educational model for the modern era, particularly in the development of educational policies that support the integration of ethical values, cross-disciplinary collaboration, and research-based innovation. By imitating the scientific spirit of the Abbasid Dynasty, modern society can create a more holistic and sustainable education system.